FUNGSI FORUM KERUKUNAN UMAT BERAGAMA (FKUB) DALAM SISTEM SOSIAL PENCIPTAAN KERUKUNAN UMAT BERAGAMA DI KABUPATEN PASAMAN BARAT - Ferdi Ferdian (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
TThis article is about the establishment of tolerance between groups of religious followers at the regencey level. FKUB, which means the forum for religious harmony, have been established since 2006 to maintain the religious harmony among different religious followers in Indonesia. The forum was formed after a joint policy between the Minister of Religious Affairs and the Minister of Internal Affairs. The joint policy was constructed based on the view that the governmental effort on facilitating communication and dialog between different religious leaders will prevent the horizontal conflict between religious followers. This paper is aimed to investigate the FKUB’s role in establishing tolerance between groups of the religious followers in West Pasaman Regency. This paper is mainly focused on investigating the activities organized to maintain the inter-religious harmony in the regency. By using indepth interview technique and the Functional Structural Theory are used and implemented to portray the contribution of FKUB to the establishment of the religious harmony. It is found that FKUB conducts various activities in playing their role, that are facilitating a series of dialogue between religious groups and community leaders and conducting investigations and mediations as they are needed. FKUB of West Pasaman Regency integrate itself to the social system of the community which allow them to manage the inter-religious harmony in West Pasaman. Artikel ini adalah tentang penciptaan toleransi antar pemeluk agama pada tingkat kabupaten. Forum Kerukunan Ummat Beragama (FKUB) mulai dari tingkat nasional sampai pada tingkat kabupaten/ kota didirikan oleh pemerintah setelah reformasi (2006) untuk menciptakan kerukunan umat beragama di Indonesia. Kebijakan ini merupakan kebijakan bersama Menteri Agama dan Menteri Dalam Negeri didasarkan pada pandangan bahwa konflik-konflik agama yang terjadi dapat dikendalikan dengan mewadahi komunikasi antar pemuka-pemuka agama yang berbeda. Artikel ini akan menyampaikan hasil penelitian tentang fungsi FKUB menciptakan toleransi antar umat bergama di Kabupaten Pasaman Barat, yang terdiri dari pemeluk agama yang berbeda. Fokus penelitian pada aktivitas-aktivitas yang dilakukan untuk menjaga kerukunan antar umat beragama di Kabupaten Pasaman Barat. Dengan menggunakan teknik wawancara mendalam dan Teori Struktural Fungsional, artikel ini akan menunjukkan bahwa untuk menciptakan kerukunan antar umat beragama FKUB Pasaman Barat melakukan berbagai kegiatan yakni melakukan dialog dengan tokoh agama dan tokoh masyarakat, menampung dan menyalurkan aspirasi masyarakat, melakukan investigasi dan mediasi. Dalam melakukan berbagai aktivitas-aktivitas, FKUB Pasaman Barat menduduki posisi integrasi dalam sistem sosial kerukunan beragama di Kabupaten Pasaman Barat dan memainkan peranan sebagai penjaga kerukunan antar umat beragama.